Plankton biogeography in the 21st century and impacts of climate change: advances through genomics - Frémont, Paul; Gehlen, Marion; Jaillon, Olivier (Comptes Rendus Biologies, 2023)
This article summarizes recent advances in our knowledge of plankton biogeography obtained by genomic approaches and the impacts of global warming on it. Large-scale comparison of the genomic content of samples of different plankton size fractions revealed a partitioning of the oceans into genomic provinces and the impact of major oceanic currents on them. By defining ecological niches, these provinces are extrapolated to all oceans, with the exception of the Arctic Ocean. By the end of the 21st century, a major restructuring of these provinces is projected in response to a high emission greenhouse gas scenario over 50% of the surface of the studied oceans. Such a restructuring could lead to a decrease in export production by 4%. Finally, obtaining assembled sequences of a large number of plankton genomes defining this biogeography has allowed to better characterize the genomic content of the provinces and to identify the species structuring them. These genomes similarly enabled a better description of potential future changes of plankton communities under climate change.